Evaluating Risks in an Outcome-Based Education Assessment Information System: A Qualitative Case Study in Higher Education - Olivia Wardhani; Pringgo Widyo Laksono (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify, categorize, and prioritize risks in an Outcome-Based Education (OBE)-based assessment information system related to learning outcome evaluation, Program Learning Outcomes–Course Learning Outcomes assessment processes, and institutional quality assurance implementation in higher education. Methodology: This study used a qualitative case study approach with the Project Management Body of Knowledge® Guide Sixth Edition Project Risk Management framework, Risk Breakdown Structure (RBS), and qualitative probability–impact matrix. Data collection methods included document analysis, direct observation, semi-structured interviews, prototype system review, and Program Learning Outcomes–Course Learning Outcomes mapping validation. Main Findings: Eighteen risks were identified across technical, data-related, operational, human resource, curriculum-related, and infrastructure categories. High-priority risks involved inconsistencies in Program Learning Outcomes–Course Learning Outcomes mapping and assessment weighting structures. Extreme risks included system integration limitations, developer dependency, and infrastructure readiness issues affecting learning outcome evaluation and assessment consistency. Novelty/Originality of this study: This study presents a structured qualitative risk analysis framework for Outcome-Based Education (OBE)-based assessment information systems by integrating educational evaluation perspectives with project risk management approaches. The study highlights how organizational, operational, and data-related risks influence learning outcome assessment validity and institutional quality assurance processes.